2012
DOI: 10.1073/pnas.1205982109
|View full text |Cite
|
Sign up to set email alerts
|

DBL-1, a TGF-β, is essential for Caenorhabditis elegans aversive olfactory learning

Abstract: The TGF-β superfamily is conserved throughout metazoan, and its members play essential roles in development and disease. TGF-β has also been implicated in adult neural plasticity. However, the underlying mechanisms are not well understood. Here we report that DBL-1, a Caenorhabditis elegans TGF-β homolog known to control body morphology and immunity, is essential for aversive olfactory learning of potentially harmful bacteria food. We show that DBL-1 generated by the AVA command interneurons, which are critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 43 publications
(57 reference statements)
2
71
0
Order By: Relevance
“…4E,F). Expressing the SMA-6 receptor, using previously reported strains able to rescue sma-6 aversive olfactory learning defects (Zhang and Zhang, 2012), in hypodermis (using the col-12
Fig. 4. HEN-1 and the DBL-1/Sma pathway regulate food-avoidance behavior.
…”
Section: Resultsmentioning
confidence: 99%
“…4E,F). Expressing the SMA-6 receptor, using previously reported strains able to rescue sma-6 aversive olfactory learning defects (Zhang and Zhang, 2012), in hypodermis (using the col-12
Fig. 4. HEN-1 and the DBL-1/Sma pathway regulate food-avoidance behavior.
…”
Section: Resultsmentioning
confidence: 99%
“…INS-6 secreted from ASI antagonizes expression of another insulin-like peptide, INS-7, in a second set of neurons, and the authors hypothesize that secreted INS-7, in turn, negatively affects aversive learning by antagonizing the insulin receptor DAF-2 [25]. In a second study, the secreted TGF-b ligand DBL-1 was also shown to be necessary for the aversive learning response on P. aeruginosa [26]. Thus, at least three neuropeptides promote aversive learning on P. aeruginosa, two of which -INS-6 and INS-7 -act through the aforementioned ADF modulatory circuit.…”
Section: Microbial Cues and Chemosensationmentioning
confidence: 94%
“…DAF-7 functions in the neuroendocrine regulation of diverse aspects of organismal development and physiology, including the dauer developmental decision, foraging and aggregation behaviors, quiescence, metabolism, and longevity (de Bono et al, 2002; Gallagher et al, 2013; Greer et al, 2008; Milward et al, 2011; Shaw et al, 2007; Swanson and Riddle, 1981). In addition, another C. elegans TGF-β-family ligand, DBL-1, has been shown to regulate olfactory aversive learning and antifungal defenses (Zhang and Zhang, 2012; Zugasti and Ewbank, 2009). Expression of daf-7 is limited to the ASI pair of chemosensory neurons and has been shown to respond to the availability of bacterial food (Ren et al, 1996; Schackwitz et al, 1996).…”
Section: Introductionmentioning
confidence: 99%